2015
DOI: 10.5194/se-6-583-2015
|View full text |Cite
|
Sign up to set email alerts
|

Soil–landform–plant-community relationships of a periglacial landscape on Potter Peninsula, maritime Antarctica

Abstract: Abstract. Integrated studies on the interplay between soils, periglacial geomorphology and plant communities are crucial for the understanding of climate change effects on terrestrial ecosystems of maritime Antarctica, one of the most sensitive areas to global warming. Knowledge on physical environmental factors that influence plant communities can greatly benefit studies on the monitoring of climate change in maritime Antarctica, where new ice-free areas are being constantly exposed, allowing plant growth and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 17 publications
0
15
0
6
Order By: Relevance
“…In our study, recruitment from different reproduction modes showed different responses to environmental factors. It is well known that individuals coming from asexual reproduction are nourished by soil resources obtained via their mother plants (Pitelka and Ashmun, 1985;Marshall, 1990;de Kroon et al, 1996), and that these plants can absorb more water and nutrients from the soil through their flourishing roots. These studies might help explain why SM and OM depicted a negative effect on surviving ramet density in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, recruitment from different reproduction modes showed different responses to environmental factors. It is well known that individuals coming from asexual reproduction are nourished by soil resources obtained via their mother plants (Pitelka and Ashmun, 1985;Marshall, 1990;de Kroon et al, 1996), and that these plants can absorb more water and nutrients from the soil through their flourishing roots. These studies might help explain why SM and OM depicted a negative effect on surviving ramet density in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Soil and vegetation are key components in the earth system (Raven et al, 1986;Poelking et al, 2015). In spite of this, abusive exploitation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Understood soil diversity is a relevant task, especially considering that plant distribution is conditionate by soil properties [8,9]. Soil influences plant physiognomies in Brazilian Savanna (Cerrado) [10], Restinga forest [11], Amazonia rainforest [12,13], Tundra [14] and other biomes around the world [15,16]. However, species diversity in Caatinga is poorly know [17] and strictly attributed to climatic conditions [1820].…”
Section: Introductionmentioning
confidence: 99%
“…Plants are important in the Earth system (Lieskovsky and Kenderessy, 2014;Berendse et al, 2015;Cassinari et al, 2015;Poelking et al, 2015;Beyene, 2015;Zhao et al, 2015). The weaker correlation between NDVI and soil moisture for the entire year might be explained by the large column depth (1.6 m) used to model soil moisture data (Fan and van den Dool, 2004).…”
Section: Correlations Analysismentioning
confidence: 99%